Penggunaan POE-inqury melalui blended learning terhadap hasil belajar siswa pada pembelajaran materi sistem respirasi - Triara Noerhandayani; Suhara Suhara; Rini Solihat (Department of Biology Education, Universitas Pendidikan Indonesia, 2021)
The purposes of this research were to analyze the improvement of students’ learning outcomes after participating in learning the respiratory system using POE-Inquiry through Blended Learning by Google Classroom. The research used Quasy Experiment Method. The data in this research were collected using multiple-choice questions to find out students’ level of understanding and outcome. The questionnaire supports students’ responses to the lessons. The result shows that the teaching process using POE-Inquiry through Blended Learning by Google Classroom contribute and support the progress of student learning outcome, can be seen with the result of largest of N-gain score index: first of N-gain score as much as 22,2% low category; acquisition of second N-gain score as much as 44,4% in the high category; and third N-gain score as much as 66,7% in the medium category. The result of Mann-Whitney U test on the final posttest found that the p-value (0,548) is greater than α (0.05), so it can be concluded that does not have a significant difference between Blended Learning and without Blended Learning (full face to face). Nearly all students gave positive feedback on learning the respiratory system using POE-Inquiry through Blended Learning by Google Classroom.